Self-Healing of Cracks in Concrete using Bacillus cibi with Different Encapsulation Techniques - Christian Orozco; Ivan Jan A. Urbino (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
One of the main challenges related to concrete is the formation of cracks, which can greatly diminish its strength and decrease its service life. Repair costs to mitigate these cracks can be high. This study investigated the use of Bacillus cibi to produce a self-healing bio-concrete capable of repairing cracks by itself through microbial activity. Bacteria were introduced into concrete by direct incorporation and encapsulating it in lightweight aggregates (LWA) and diatomaceous earth (DE). Samples of concrete cylinders were tested to quantify crack healing, compressive strength, and water permeability. The results showed that bio-concrete prepared with the LWA encapsulation method was able heal the largest crack width at 0.541 mm after 35 days of wet-dry cycle. Bio-concrete produced from bacteria with no encapsulation exhibited significant enhancement in 28-day compressive strength (57.28 MPa) compared to normal concrete (54.78 MPa) and produced the highest hydraulic conductivity recovery at 85.04% after 35 days of healing. The XRD analysis showed that the bacteria did not cause any major changes to the concrete.